Ekstrakurikuler Karawitan: Media Pembelajaran dan Pelestarian Budaya di SMA 1 Padang Panjang - Firdaus, Firdaus; Firman, Firman; Admiral, Admiral; Arnailis, Arnailis; Elizar, Elizar (Universitas Lampung, 2024)
The aim of this study is to explore efforts to preserve the art of karawitan through extracurricular programs at SMA 1 Padang Panjang, with a specific focus on the use of the traditional musical instrument Pupuik Batang Padi. Karawitan, which includes traditional music and other traditional instruments, holds significant philosophical, aesthetic, and spiritual values within Indonesian culture. However, the influence of globalization and popular culture poses a threat to the existence of this art form among younger generations. This research adopts a descriptive qualitative approach, utilizing techniques such as observation, in-depth interviews, and documentation of extracurricular activities. The results indicate that teaching karawitan through the making and playing of Pupuik Batang Padi not only enhances students' technical skills but also fosters a sense of pride and responsibility towards their cultural heritage. The program has proven effective in strengthening students' cultural identity, instilling values of mutual cooperation, discipline, and respect for nature. Moreover, the program contributes to the preservation of Minangkabau traditional arts, with students actively bringing their skills into the public sphere by participating in local cultural events. These findings underscore the importance of integrating traditional arts into education as a medium for cultural preservation and character development in the face of globalization challenges.Keywords: Extracurricular, Karawitan, Cultural Preservation, Pupuik Batang Padi